Sources of Work-Related Stress among Nurses Working at Psychiatric Wards in Hospitals of Baghdad City - Al-Ameri, maan (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: The study intends to identify the sources of work-related stress that might face the nurses working atpsychiatric wards in Baghdad psychiatric hospitals and to find out a relationship between the levels of stress andsome demographic characteristics.Methodology: A descriptive study was achieved from the 10th of December, 2013 through the 10th of March, 2014.Non-probability purposive samples of 94 nurses who work in psychiatric wards of Baghdad psychiatric hospitalswere recruited to meet the study objectives. Psychological Stress Inventory (PSI) the Arabic version, which wasmodified by Abu Al-Hussein (2010) (20), was used. Data were analyzed by using the statistical analysis program ofSPSS 19th version. Descriptive analysis: frequencies, percentages and distribution; inferential analysis: Chi2 andcorrelation coefficient were applied.Results: The results indicate that the levels of work-related stress was found as high (37.2%), intermediate (33.0%),and low (29.8%) and the highest level of work-related stress is found in regards to the monetary domain (50.0%),work environment domain (47.9%), and political domain (45.8%)..Recommendations: The study recommends that: more male nurses to be appointed at psychiatric. To find realspecialized psychiatric nurses. To put criteria to appoint a bachelor level in nursing at these wards; engaging nursesworking at psychiatric wards in special sessions of stress management; and finally, fixing a professional criteria ofthe relation between nurses and doctors or/ and boss during the time of working at these wards